2019
DOI: 10.1108/oir-02-2017-0042
|View full text |Cite
|
Sign up to set email alerts
|

Clothing brand purchase intention through SNS

Abstract: Purpose The purpose of this paper is to investigate the intention to purchase products through clothing brands’ social network sites (SNS) based on the theory of planned behavior and uses and gratifications theory (U&G), and the moderating effects of self-image congruity (SIC). Design/methodology/approach Data were collected from 1,003 followers of their favorite clothing brands’ SNS. Data analysis was performed using structural equation modeling (SEM) and multi-group SEM analysis. The models were estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 84 publications
(156 reference statements)
2
6
0
Order By: Relevance
“…To achieve this, we investigated a novel conceptual model which explains the impact of social networking sites advertisements, on consumer purchases decision: mediated by brand. As a primary contribution, this research showed that there was a positive relationship between social networking sites advertisement and consumer purchase decision, these results are consistent with previous studies, where the researcher found that SNS had a significant direct effect on consumer purchase intention towards clothes brands in Spain (Pujadas-Hostench et al, 2019a, 2019b. These results indicated that, when the consumer realizes the clothes brand advertisement in SNS they would be willing and interested in that brands which led them make a decision in purchasing that specific clothes brand which in turn resulting in their actual baying behavior (Touchette et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…To achieve this, we investigated a novel conceptual model which explains the impact of social networking sites advertisements, on consumer purchases decision: mediated by brand. As a primary contribution, this research showed that there was a positive relationship between social networking sites advertisement and consumer purchase decision, these results are consistent with previous studies, where the researcher found that SNS had a significant direct effect on consumer purchase intention towards clothes brands in Spain (Pujadas-Hostench et al, 2019a, 2019b. These results indicated that, when the consumer realizes the clothes brand advertisement in SNS they would be willing and interested in that brands which led them make a decision in purchasing that specific clothes brand which in turn resulting in their actual baying behavior (Touchette et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Consumer perception benefits (social, informational and hedonic) exhibited significant positive effects on the attitude of online community members (perceived community attitude and AFSRP); this finding is in agreement with those of other relevant studies (Jung et al , 2014; Anderson et al , 2014). These findings support that consumers who use clothing brands’ SNS pages are looking for information about the brand and for social interaction (Pujadas-Hostench et al , 2019). Fans, thus, recognize the various levels of benefits provided by the fan group to which they belong.…”
Section: Discussionsupporting
confidence: 69%
“…The apparel industry was chosen as the context for our study because customers tend to buy apparel products more than any other retail products (PwC, 2016); apparel retailers have been noted to be among the most prolific, dynamic, and successful international retailers (Frasquet et al., 2017); the main goal of apparel retailers is to increase purchase loyalty (Cham et al., 2018; Gremler et al., 2019); scholars have shown an increasing interest in understanding the relationship between purchase intent and its determinants in the apparel industry (Neumann et al., 2020; Pujadas‐Hostench et al., 2019). To measure the research constructs, we divided the survey questionnaire into three sections.…”
Section: Methodsmentioning
confidence: 99%
“…scholars have shown an increasing interest in understanding the relationship between purchase intent and its determinants in the apparel industry (Neumann et al, 2020;Pujadas-Hostench et al, 2019). To measure the research constructs, we divided the survey questionnaire into three sections.…”
Section: Sample and Data Collectionmentioning
confidence: 99%